2018
DOI: 10.1111/ejh.13127
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab for transplant‐associated thrombotic microangiopathy in adult allogeneic stem cell transplant recipients

Abstract: Early initiation of ECU may not alter the disease process enough to restore organ function, but it may prolong survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The extensive end-organ damage seen in this cohort after treatment is more consistent with outcomes reported in an adult cohort of 10 patients treated with eculizumab for TA-TMA after allogeneic HCT. Overall survival was 60%, but only 1 patient had full organ recovery [18]. More studies are needed to examine the impact of treatment on late organ function in survivors, particularly in aHCT.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive end-organ damage seen in this cohort after treatment is more consistent with outcomes reported in an adult cohort of 10 patients treated with eculizumab for TA-TMA after allogeneic HCT. Overall survival was 60%, but only 1 patient had full organ recovery [18]. More studies are needed to examine the impact of treatment on late organ function in survivors, particularly in aHCT.…”
Section: Discussionmentioning
confidence: 99%
“…13 This has become increasingly important since the advent of a potentially disease-modifying drug, eculizumab. [14][15][16] This approach to diagnosis is challenging, because clinical features of TA-TMA are common to multiple post-HCT complications, including acute graft-versus-host disease (aGVHD) and infections. 17 These complications are also risk factors for the subsequent development of TA-TMA.…”
Section: Introductionmentioning
confidence: 99%
“…Among these included studies, five studies reported the complete response rate (CRR) for TA-TMA patients receiving Eculizumab treatment ( 19 , 20 , 24 26 ). The heterogeneity among included studies was substantial (I 2 = 73%, P < 0.01) and the pooled estimate of CRR was 32% (95%CI: 11–56%), which was much lower than overall response ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the study by Joslyn et al, the median duration between diagnosis and Eculizumab therapy was shorter, at four days, compared to other studies. Only one patient achieved a complete response and organ function was restored ( 19 ). This suggests that earlier initiation of Eculizumab may have no significant effect on restoring organ function.…”
Section: Discussionmentioning
confidence: 99%